Técnicas de inteligencia artificial en dispositivos iot - Villacrés Cango, Hjalmar Leonel (Machala: Universidad Técnica de Machala, 2021)
Internet is a technology that is growing exponentially, and from this new source of information are emerging that give way to the development of new technologies. One of them and that is gaining a lot of ground is the internet of things or IoT, a technology that has grown very quickly in recent years and this is very evident due to the great connectivity that exists between various devices and the accessibility to obtain them. Currently there are many homes that have internet access and each of them maintains connectivity between several devices using the same network, devices such as cell phones, tablets, laptops, televisions and even smart refrigerators are the ones that recently allow connecting to the Internet to share information. Users observe that the integration of these devices to the network allows a rapid manipulation of them and at the same time they take advantage of the technologies that they present, increasing the connectivity between devices and increasing the interest of the Internet of Things, contributing to the growth of the same. One of the areas in which we are immersing ourselves is in the Internet of things, to be more exact, in home automation due to the automation of smart devices. Home automation plays a very important role in the IoT because it is considered as automation, in which devices capable of connecting to the network and communicating with each other intervene, sharing fundamental information for the user and at the same time easy manipulation in the household devices. This manipulation is achieved by means of tools and platforms aimed at home automation, one of them and the most popular is Home Assistant, capable of housing home automation devices for easy handling, in addition to containing a number of tools that allow operating in an easy way. very simple. The other area that we deal with in this work is the translation of gestures originating in the Ecuadorian sign language, which at present turns out to be a barrier between people who understand the language and those who do not understand it, that is, that the translator will allow the communication of certain words, greetings and questions to text and voice. With this, we generate a low-cost system capable of providing an acceptable solution to this problem. Automation of home automation devices integrated into Home Assistant is commonly accomplished using a mobile device or laptop and this includes valuable time that can be used for some other activity. For this, in the present work it is proposed to design and implement a system that allows to recognize ten gestures for their translation into text and voice, in addition to operating domotic devices integrated in Home Assistant through the MQTT communication protocol using a particular gesture. Low-cost and easily accessible components will be used for this project.
Internet es una tecnología que va creciendo de manera exponencial, y de esta van apareciendo nuevas fuentes de información que dan paso al desarrollo de nuevas tecnologías. Una de ellas y que va ganando mucho terreno es el internet de las cosas o IoT, tecnología que ha crecido de manera muy rápida en los últimos años y esto es muy evidente debido a la gran conectividad que existe entre diversos dispositivos y la accesibilidad para obtenerlos. Actualmente son muchos los hogares que cuentan con acceso a internet y cada uno de ellos mantienen una conectividad entre varios dispositivos utilizando una misma red, dispositivos como celulares, tablets, laptops, televisores e incluso neveras inteligentes son las que recientemente permiten conectarse a Internet para compartir información. Los usuarios observan que la integración de estos dispositivos a la red permite una rápida manipulación de los mismos y a la vez sacan provecho de las tecnologías que estos presentan, creciendo más la conectividad entre dispositivos y aumentando el interés del Internet de las cosas aportando en el crecimiento del mismo. Uno de los ámbitos en el cual nos estamos sumergiendo es en el Internet de las cosas, para ser más exactos, en la domótica debido a la automatización de dispositivos inteligentes. La domótica juega un papel muy importante en el IoT debido a que el mismo se lo considera como automatización, en la que intervienen dispositivos capaces de conectarse a la red y comunicarse entre sí compartiendo información fundamental para el usuario y a la vez una fácil manipulación en los dispositivos del hogar. Esta manipulación se logra por medio de herramientas y plataformas orientadas a la domótica, una de ellas y la más popular es Home Assistant capaz de alojar dispositivos domóticos para su fácil manipulación, además de que el mismo contiene un sinnúmero de herramientas que permiten operar de manera muy sencilla. El otro ámbito que tratamos en el presente trabajo es la traducción de gestos originarios de la lengua de señas ecuatorianas que en el presente resulta ser una barrera entre las personas que entienden la lengua y las que no la comprenden, es decir, que el traductor permitirá la comunicación de ciertas palabras, saludos y preguntas a texto y voz. Con esto generamos un sistema de bajo costo capaz de brindar una solución aceptable a este problema. La automatización de dispositivos domóticos integrados en Home Assistant comúnmente se logra utilizando un dispositivo móvil o una laptop y esto incluye tiempo valioso que puede ser usado para realizar alguna otra actividad. Para ello, en el presente trabajo se plantea diseñar e implementar un sistema que permita reconocer diez gestos para su traducción a texto y voz, además de operar dispositivos domóticos integrados en Home Assistant por medio del protocolo de comunicación MQTT utilizando un gesto en particular. Para este proyecto se utilizarán componentes de bajo costo y de fácil accesibilidad.
Keywords: IOT; DOMOTICA; MACHINE LEARNING; ACELEROMETRO